2010
DOI: 10.1007/s00330-009-1707-9
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted biopsies under MR guidance: results of 72 procedures

Abstract: MRI-guided VAB represents an accurate tool for the histological diagnosis of lesions visible only at MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
4
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 33 publications
7
28
4
4
Order By: Relevance
“…Both frequency of high-risk lesions at MRgVABB and underestimation rates in our study are higher than previously reported in other studies (Table 4) evaluating outcomes of MR-guided breast biopsy [11,12,29,31,32]. This might be explained by the high pretest probability for breast cancer in our study population, which in addition to asymptomatic women undergoing screening MRI included a substantial proportion of diagnostic cases and patients with a personal history of breast carcinoma.…”
Section: Discussioncontrasting
confidence: 71%
“…Both frequency of high-risk lesions at MRgVABB and underestimation rates in our study are higher than previously reported in other studies (Table 4) evaluating outcomes of MR-guided breast biopsy [11,12,29,31,32]. This might be explained by the high pretest probability for breast cancer in our study population, which in addition to asymptomatic women undergoing screening MRI included a substantial proportion of diagnostic cases and patients with a personal history of breast carcinoma.…”
Section: Discussioncontrasting
confidence: 71%
“…The mean duration of vacuum assisted biopsy was reported as 65 min by Malhaire et al (26), and as 35 min by Tozaki et al (24). The mean duration of vacuum assisted biopsy was determined as 38 min (24-69 min) in our study, which was in concordance with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Current modern technological advances such as contrastenhanced MRI and vacuum core biopsy could potentially assist in providing a more accurate diagnosis of both extent of disease and presence of invasion in a significant proportion of cases, 29,30 particularly in cases of ER negative DCIS since our study suggests that underestimation of disease extent might be related to ER status. High-grade DCIS may be focally uncalcified, leading to underestimation of disease extent and an increased probability of the requirement for more than one therapeutic operation.…”
Section: Discussionmentioning
confidence: 77%